Prostate cancer survivorship, deaths, and health care management. Issue 16 (21st April 2021) - Bauer, Joseph E.
Abstract : In this issue of Cancer, Weiner et al present a US population–based analysis of the causes of death in prostate cancer survivors. Thoughts are presented on how their results can bring value to clinical practitioners, especially primary care physicians, who work on managing the health care of prostate cancer survivors in the complex environment of the COVID‐19 pandemic.